El despido intempestivo de los trabajadores en el sector privado de la Ciudad de Loja, genera inestabilidad laboral contraveniendo el derecho al trabajo establecido en el Código de Trabajo - Alvarado Zapata, Jhon Armando (2016)
In this paper it gets to discussion, that the untimely dismissal violates the rights of workers laid down in the constitution and the labor code in Art. 326 of the Constitution and Art. 4 of the Labour Code The dismissal is a unilateral form of termination of the employment relationship, is not defined in law or referred to in Article 169 of the Labor Code as grounds to terminate the individual employment contract, however, can be defined as an act unilateral and unmotivated expressed by external acts and reflects the will of the employer to terminate the contract. Annotated what we emphasize that the worker is removed without just cause; or when habiéndola, not the procedure established by law to terminate the employment relationship, as in the case of the employer not get the nod is observed. There are many abuses by employers against workers who are sanctioned by the Labour Code Article 188, which are indicated compensation for unfair dismissal, but it turns out that these sanctions and compensation provided for in that legal body does not meet the expectations repair the economic damage caused to the worker to stay in unemployment actually, and therefore they are derisory not constitute any obstacle to prevent the employer violates the laws. Being necessary a reform proposal aimed at protecting the rights of workers are guaranteed by our Constitution of the Republic of Ecuador, like international treaties, but are violated by the employer, such reform is aimed at improving labor relations between employers and workers as a brake on the arbitrariness of certain employers.